Isolation of Streptococcus spp from nile tilapia (Oreochromis niloticus) and quality of water in hapas nets in North Region of Parana State, Brazil - Salvador, Rogério; Müller, Ernst Eckehardt; Leonhardt, Júlio Hermann; Pretto-Giordano, Luciene Garcia; Dias, Juliana Alves; Freitas, Júlio César de; Moreno, Aleksey Machado (Semina: Ciências Agrárias, 2003)
This study evaluated 12 intensive breed of Nile tilapia (Oreochromis niloticus) in four properties localized in the north of Parana State, Brazil. In the period of 13 months, 71 fishes were collected and analyzed of hapas nets that presenting morbidity and mortality of tilapias. Parallel, to evaluate the quality of the water of these hapas nets, there was measured the temperature, dissolved oxygen, pH, alkalinity, nitrite and ammonia. Of the 71 fishes, were collected 220 biological samples. 17 (23.94%) fishes were positive for Streptococcus spp. Of the 53 biological samples from 17 fishes, in 24 (45.28%) were isolated streptococci. The main clinical signs and macroscopic lesions in the fishes with isolation of Streptococcus spp. were hepatomegaly and splenomegaly, skin lesion and base of the fins and exoftalmia with cornea opacity. The higher incidence of infections caused by streptococci happened in the months with higher temperatures, mainly in the transition period winter for spring. The values of dissolved oxygen, pH, alkalinity, nitrite and ammonia of the water were normal.